2017
DOI: 10.1371/journal.pone.0175675
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced offspring predisposition to steatohepatitis with maternal high-fat diet is associated with epigenetic and microbiome alterations

Abstract: ObjectiveNon-alcoholic fatty liver disease (NAFLD) is an important co-morbidity associated with obesity and a precursor to steatohepatitis. However, the contributions of gestational and early life influences on development of NAFLD and NASH remain poorly appreciated.MethodsTwo independent studies were performed to examine whether maternal over-nutrition via exposure to high fat diet (HFD) leads to exacerbated hepatic responses to post-natal HFD and methionine choline deficient (MCD) diets in the offspring. Off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
157
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(166 citation statements)
references
References 45 publications
7
157
1
1
Order By: Relevance
“…Birth weight was obtained from N = 63 studies ( N = 6530 offspring), one study was included twice in meta‐analysis since they reported on two separate cohorts . In six studies, data on birth weight was not extractable . There was no difference in birth weight between offspring of mothers with obesity and offspring of mothers with a normal weight, SMD −0.05 [95% CI −0.17; 0.07], I 2 = 74% (figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Birth weight was obtained from N = 63 studies ( N = 6530 offspring), one study was included twice in meta‐analysis since they reported on two separate cohorts . In six studies, data on birth weight was not extractable . There was no difference in birth weight between offspring of mothers with obesity and offspring of mothers with a normal weight, SMD −0.05 [95% CI −0.17; 0.07], I 2 = 74% (figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Body weight was measured at age 4 days up to 13 months. We were unable to extract outcome data from four studies . Offspring's body weight was increased following maternal obesity, SMD 0.76 [95% CI 0.60; 0.93], I 2 = 86% (figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the portal vein that connects the liver to the gastrointestinal tract, the liver is exposed to the influence of the gut microbiome. Perturbations of the gut microbiome, coupled with disturbances in gut barrier function, have been associated with common liver disorders, such as non-alcoholic fatty liver disease [138][139][140], non-alcoholic steatohepatitis [139,[141][142][143][144][145][146][147][148][149][150][151][152], alcoholic liver disease [139,140,142,145,147,148,150,151,[153][154][155][156][157][158][159][160][161][162][163][164], and liver cirrhosis [165][166][167][168][169][170]. Thus, the microbiome serves as a modulator of liver rhythmic functions.…”
Section: Liver Functionmentioning
confidence: 99%
“…In a recent mouse study, maternal HFD detrimentally altered gut microbiome profiles in the offspring, which contributed to development of obesity, steatohepatitis and its progressive diseases in the offspring (Paul et al, 2016, 2018; Wankhade et al, 2017). Intriguingly, studies in non-human primates have shown that maternal HFD led to persistently reduced abundance of Campylobacter species in the offspring gut compared to the control diet group even though the primates were weaned and switched to control diet for 6 months ( Table 2 ; Ma et al, 2014).…”
Section: Maternal Diet Epigenetics and Gut Microbiome In Developmentmentioning
confidence: 99%